Polimerisasi Eugenol Minyak Daun Cengkeh Hasil Redistilasi, Ekstraksi, dan Fraksinasi Menggunakan Katalis Asam Sulfat Pekat - Sudarlin Sudarlin; Winarto Haryadi (Syarif Hidayatullah State Islamic University, 2017)
Polymerization of purified eugenol from clove leaf oil using concentrated sulfuric acid as catalyst has been done in this research. Clove leaf oil was purified by vacuum redistillation, acid-base extraction, and vacuum fractionation to yield eugenol. The eugenol was polymerized with concentrated sulfuric acid in ratio 1: 2. Polyeugenol from eugenol of clove leaf oil resulted from redistillation, extraction, and fractionation is in solid form (yield: 88.14%); from redistillation and extraction is also in solid form (yield: 86.15%); from redistillation clove leaf oil is in gel form (yield: 100.29%). Structure of polyeugenol was determined by infrared spectrophotometer and characterized by thin layer chromatography (TLC). Molecular weight of the product was calculated by viscometry method.DOI: http://dx.doi.org/10.15408/jkv.v0i0.4685